“We Deserve the Dignity of Being Housed”: LGBTQ2+ Housing Experiences in Fresno County, California - Katherine Fobear (International Journal on Homelessness)
Lesbian, gay, bisexual, transgender, queer, and Two-Spirit (LGBTQ2+) adults experience homelessness and housing precarity at greater rates than their cisgender and heterosexual counterparts. Although LGBTQ2+ adult individuals make up a significant portion of the homeless population, the oppression and barriers they experience are often invisiblized. Research on LGBTQ2+ housing experiences and homelessness in the United States has predominantly focused on individuals in larger urban centers and on homeless LGBTQ2+ youth. This study focuses on the housing experiences of LGBTQ2+ adults living in Fresno, California.  The City of Fresno and Fresno County are situated within the Central Valley, a largely rural area with limited resources that has one of the fastest-growing poverty rates in the state. Understanding LGBTQ2+ adult housing experiences not only provides critical insight into the housing barriers in Fresno but also provides a template for similar research in other mixed urban and rural areas. Using empirical data, this study provides a deeper understanding regarding queer precarity and ontological security surrounding housing and LGBTQ2+ communities.